Novel Aspects of Genetics, Molecular Biology and Clinical Oncology of Sarcomas - Houfková, K; Hatina, J (Klinicka onkologie, 2020)
The Connective Tissue Oncology Group Annual Meeting 2018 (CTOS 2018) took place in Rome from 4 to 17 November 2018, and the 39th Plenary Meeting of the Scandinavian Sarcoma Group (SSGM 2019) was held in Bergen from 8 to 10 May 2019. These two large international conferences brought together an overwhelming majority of molecular and clinical specialists in the sarcoma field, especially those working on soft tissue sarcoma. Topics discussed on the conferences included, among others, sarcoma genetics, clinical and molecular subclassification, targeted therapy, clinical prognostication, and new experimental sarcoma models. A large ongoing international study on germinal sarcoma genetics was presented, the interim results of which revealed the extremely complex nature of genetic disposition to sarcoma, and, surprisingly, a rather prominent place among predisposing genes for those coding for structural telomere constituents. Fusion oncogenes dominate somatic sarcoma genetics, especially because of their origin and impact on sarcoma clinical behaviour, and are especially relevant for karyotypically simple paediatric sarcomas. A crucial issue in karyotypically complex sarcomas are the efforts being made to obtain a subclassification of sarcoma, other than those based on pathology, using either the clinical characteristics of sarcomas (uterine leiomyosarcoma vs. soft tissue leiomyosarcoma) or specific gene expression profiles (molecular subtypes in undifferentiated pleiomorphic sarcoma), which showed that molecular characterization can open the way for subtype specific therapies. Other examples of where this type of strategy can be applied include gastrointestinal stromal tumours, infantile fibrosarcoma, and inflammatory myofibroblastic tumours, where targeted therapy could be conceived based on the actionable mutations identified. Attempts in this direction have been made also for clear cell sarcoma and dedifferentiated liposarcoma, albeit the effectiveness of molecular-targeted treatments for these sarcomas is still poor, and progress in the treatment of osteosarcoma is still rather slow. Actually, the platelet-derived growth factor signalling system holds a prominent position in searches for targeted therapies, not only against rare sarcoma types, where are activated by mutations (some gastrointestinal stromal tumours, infantile hereditary myofibromatosis, and dermatofibrosarcoma protuberans), but also against other more usual sarcoma types, where the blocking anti-PDGFRα-antibody olaratumab has been successfully integrated into combinatorial chemotherapeutic regimens. In the field of clinical prognostication, remarkable progress in sarcoma nomograms was reported. Interesting results were also presented in the area of new experimental sarcoma models. Participation on both scientifi c conferences and all the experimental work leading to the presented sarcoma models were supported by the Czech Science Foundation project No. 17-17636S. The authors declare they have no potential conflicts of interest concerning drugs, products, or services used in the study. The Editorial Board declares that the manuscript met the ICMJE recommendation for biomedical papers. Submitted: 20. 9. 2019 Accepted: 6. 11. 2019.
Keywords: genetic predisposition; Soft Tissue Neoplasms; cílená molekulární terapie; lidé; sarkom; nádory měkkých tkání; Sarcoma; chondrosarcoma; experimental sarcoma models; targeted therapy; Molecular Targeted Therapy; prognostic nomograms; molecular subtypes; soft tissue sarcomas; osteosarcoma; Humans